IMPLEMENTATION OF FUZZY SELECTION OF EQUIPMENT IN INFORMATION NETWORK DESIGN SYSTEM - Chuykova, Elena Nikolayevna (Advanced engineering research (Rostov-na-Donu, Russia), 2014)
The implementation of the equipment selection process in the information network design system on the basis of fuzzy criteria is considered. The selection is made in the relational database by fuzzy SQL-queries generated in the design system program shell. The algorithm of the fuzzy SQL-queries assignment is proposed. An example of constructing a fuzzy query to select the best equipment in terms of price and quality is given. A fragment of the graphic system interface which contains an equipment selection window is presented. The described method of performing fuzzy queries is applicable to the implementation of a fuzzy search in various subject areas, it does not require any additional knowledge in fuzzy logic, and it automates the membership function formation process of the linguistic variable terms. The future activities will be linked to the expansion of the system interface capabilities on the direct designing of the fuzzy queries by a user.